2013
DOI: 10.1002/cncy.21369
|View full text |Cite
|
Sign up to set email alerts
|

Does speculum lubricant affect liquid‐based Papanicolaou test adequacy?

Abstract: BACKGROUND:There is a paucity of data on the effect of vaginal lubricants on specimen adequacy in the era of liquidbased Papanicolaou (Pap) tests. Current manufacturer recommendations advise against the use of lubricants, especially those that contain carbomers or carbopol polymers. There is, however, no conclusive evidence to support this recommendation. Moreover, the data that does exist is conflicting. METHODS: Retrospective review was performed of all liquidbased Pap tests collected between January 2010 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Other studies also have reported similar observations. [ 6 24 25 ] Additional significant etiologic factors associated with high unsatisfactory rate were association with atrophic changes and blood.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also have reported similar observations. [ 6 24 25 ] Additional significant etiologic factors associated with high unsatisfactory rate were association with atrophic changes and blood.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, quando utilizado lubrificante contendo carbômeros, uma taxa significativamente maior de amostras (26.9%) se mostrou inadequada quando comparada ao grupo que fez uso de lubrificantes sem essa substância (1,7%). (LIN, 2014)…”
Section: Materiais E Métodosunclassified
“…Relatedly, the need for and effect of lubrication (either supplemental lubrication or the lubrication that already comes placed on the condoms) with these methods needs to be studied. In the case of Pap smears, this is especially important because some fear that lubricated speculums cause artifact on the samples making interpretation di cult [52][53][54]; However, many others disagree, believing this fear is unsubstantiated or that the effect is small compared to the bene t of pain reduction [4,55,56]. Either way, the results of prior studies might not hold in the case of lubricated condoms, especially as some have found the effect of lubrication of Pap smear quality to depend on the material properties of the lubrication [54].…”
Section: Limitations and Areas For Workmentioning
confidence: 99%